Improved annular mode variability in a global atmospheric general circulation model with 16 km horizontal resolution. Issue 18 (16th September 2013) - Palipane, Erool; Lu, Jian; Chen, Gang; Kinter, James L.
Abstract : [1] In an attempt to assess the benefit of resolving the subsynoptic to mesoscale processes, the spatial and temporal characteristics of the annular modes (AMs), in particular those related to the troposphere‐stratosphere interaction, are evaluated for moderate and high horizontal resolution simulations with the European Centre for Medium‐Range Weather Forecast Integrated Forecast System global atmospheric general circulation model in comparison with the reanalysis. Notably, the performance with the high horizontal resolution (T1279 truncation, 16 km) version of the model is relatively more skillful than the moderate resolution (T159 truncation, 125 km) on most metrics examined, including the variance of the AMs at different seasons of the year, the intrinsic e ‐folding time scales of the AMs, and the downward influence from the stratosphere to troposphere in the AMs. Moreover, the summer Southern Annular Mode is more persistent in the high resolution and projected to respond in a greater magnitude to climate change forcing than the moderate resolution. Key Points: high resolution with best fidelity in annular modes. Improved key characteristics of the AM with hi‐resolution. Stronger projection of the SH jet changes with hi‐res version.